A NEW SPECIES OF NEPENTHES (NEPENTHACEAE) AND ITS NATURAL HYBRIDS FROM ACEH, SUMATRA, INDONESIA - Malcolm Victoriano (REINWARDTIA, 2021)
VICTORIANO, M. 2021. A new species of Nepenthes (Nepenthaceae) and its natural hybrids from Aceh, Sumatra, Indonesia. Reinwardtia 20(1): 17–26. — A new species of Nepenthes (Nepenthaceae) from Aceh Province, Indonesia, Nepenthes  longiptera  Victoriano is herein described and illustrated. The species is unique among all other Nepenthes in  Sumatra  by  the  presence  of  wings  on  its  upper  pitchers. Comprehensive  description, photographs,  geographical distribution  and  preliminary  IUCN  conservation  assessment  are  provided  for  the  new  species.  Hybrids  of  this  new taxon with other species are also reported in this paper.